2014
DOI: 10.1016/j.psychres.2014.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic fitness and body mass index in individuals with schizophrenia: Implications for neurocognition and daily functioning

Abstract: Previous reports indicate that among healthy individuals low Aerobic Fitness (AF) and high Body-Mass Index (BMI) predict poor neurocognition and daily-functioning. It is unknown whether these associations extend to disorders characterized by poor neurocognition, such as schizophrenia. Therefore, we compared AF and BMI in individuals with schizophrenia and non-clinical controls, and then within the schizophrenia group we examined the links between AF, BMI, neurocognition and daily-functioning. Thirty-two indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 66 publications
8
83
3
Order By: Relevance
“…Therefore, our results may not represent all schizophrenia with diabetes's situation. Fifth, studies showed that aerobic fitness could improve neurocognition in multiple domains in individuals with schizophrenia [62]. In our currently study, although individuals with schizophrenia have an opportunity of about physical exercise every day, however, we did not record about the details of aerobic exercise for individuals with schizophrenia.…”
Section: Accepted M Manuscriptmentioning
confidence: 82%
“…Therefore, our results may not represent all schizophrenia with diabetes's situation. Fifth, studies showed that aerobic fitness could improve neurocognition in multiple domains in individuals with schizophrenia [62]. In our currently study, although individuals with schizophrenia have an opportunity of about physical exercise every day, however, we did not record about the details of aerobic exercise for individuals with schizophrenia.…”
Section: Accepted M Manuscriptmentioning
confidence: 82%
“…Investigating cardiorespiratory fitness among people with SMI is of considerable clinical interest given its associations with reduced psychiatric symptoms and cognitive deficits in SMI populations [12] and given the increasing focus on lifestyle interventions as integrated components of standard care for various mental disorders [13][14][15][16][17][18]. In addition, two recent meta-analyses demonstrated that exercise interventions significantly improve cardiorespiratory fitness in people with schizophrenia [19] and in people with MDD [20].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity cannot replace traditional treatments of serious psychiatric illnesses, but could play an important part of the treatment process (Kimhy 2014). We reported reductions in PANSS general psychopathology symptoms post-exercise.…”
Section: Positive Impact Of Prescribed Physical Activity On Symptoms mentioning
confidence: 99%